Comparison of factors associated with desaturation in prehospital emergency anaesthesia in primary and secondary retrievals. Issue 8 (12th November 2014) - Wimalasena, Yashvi H; Corfield, Alasdair R; Hearns, Stephen
Abstract : Objective: To investigate the incidence and factors associated with desaturation related to emergency intubations within an aeromedical retrieval service pertaining to both primary prehospital and secondary interhospital missions. Methods: A retrospective analysis of all rapid sequence intubations (RSI) was performed by the Emergency Medical Retrieval Service over a 4.5-year period (June 2008–November 2012). For each RSI, clinical indication for RSI, age, sex, traumatic or medical diagnosis, team leader specialty, Cormack and Lehane (C-L) grade of laryngoscope view, attempts at intubation, desaturation and hypotension was analysed. A multiple logistical regression analysis was constructed using the factors identified in the univariate logistical regression using a backward stepwise model. Results: During the study period, a total of 1423 missions were carried out. 1088 of these missions were secondary retrievals and 335 were primary prehospital missions. 208 patients required RSI during the study period. Our data show that 15.4% of all anaesthetised patients had a desaturation during emergency anaesthesia. This included 11.3% of primary prehospital patients and 16.8% of secondary retrieval patients (95% CI −5.0% to 15.8%). 7.9% of patients had an episode of hypotension during RSI. Univariate associations for desaturation were more than one attempt at intubation and a C-L grade III or worse view. Multivariate analysis showed only C-L grade III or worse view as an independent risk factor for desaturation. Conclusions: Desaturation was not more common in secondary retrieval patients. Multiple attempts at intubation and a poor laryngoscopic view at intubation were associated with desaturation during RSI.